The effectiveness of krwanjang game implementation on sepak sila's skills in sepak takraw game at Surabaya sepak takraw academy - Muhyi, Muhammad; Hanafi, Muh; Asgi Sukmana, Abdian; Darma Utamayasa, I Gede; Rangga Prastyana, Brahmana (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
Krwanjang game is a game designed to develop basic skills of playing sepak takraw from an early age. The purpose of the study was to determine the game's effectiveness in improving the skills of sepak takraw players at the sepak takraw academy in Surabaya. The research method uses quantitative research. The population is all academy students and a sample of 11 students from the Surabaya Sepak Takraw Academy. The research design used a randomized pre-test post-test design, the type of design carried out by giving pre-test before treatment and post-test after treatment in the experimental group. The research data collection used several tests, including left-footed and right-footed sepak sila during pre-test and post-test. The data analysis technique is the analysis of variance (ANOVA) to determine the effectiveness level. The results showed that after the left and right-footed pre-test was conducted, they were treated with the krwanjang game and ended with the post-test of the sepak sila. From the data obtained and analyzed by ANOVA the results had a significant effect from the pre-test of 0.08 to 0.12 in the post-test. The research concludes that the sepak kwranjang game effectively improves the sepak sila skills of the students of the Surabaya Sepak Takraw Academy. The research implication is that sports coaches or academics can apply sepak kwranjang to improve their sepak sila.